Effect of Substrate on Egg Hatchability and Survival of Carp Seeds - Helmin Dupamana; Ade Muharam; Juliana Juliana (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the effect of different substrates on egg hatchability and survival of carp (Cyprinus carpio) seeds. This research is an experiment with 4 treatments and 3 replications. The treatment of addition of substrate is A (Fibers), B (Hydrilla), C (Raffia String), D (Control) Treatment. The design used is a Completely Randomized Design (CRD) using Analysis of Variance (ANOVA). Furthermore, further tests are carried out using the Least Significant Difference Test (LSD). The results obtained indicate that each treatment has a very significant effect. The highest hatchability was found in the palm substrate treatment of 87.66%, followed by the treatment of the raffia substrate 78.42%, then the control treatment with the percentage of hatching power was 64.78% and the lowest was in the hydrilla substrate treatment with the hatchability percentage of 57.51%. While the highest survival rate of tilapia fish was found in the treatment of palm oil substrate by 73.67%, and the survival rate with the lowest percentage was in the treatment of hydrilla sp. Substrate.